Mengenal E-Book Di Perpustakaan - Fahrizandi Fahrizandi (Institut Agama Islam Negeri Salatiga, 2019)
Abstract The title of this article is to know e-books in the library, this paper aims to explain what are the types, advantages and disadvantages of e-books, then how to improve performance strategies in developing e-book collections. The results of the analysis of the literature, the library must develop a collection of e-books to meet the expectations of users of information. The types of e-books can be distinguished from the nature of access, form, and mode of production. The advantages of e-books are 1) fast traceability; 2) more frequent modifications; 3) portability; 4) variations; 5) legibility; 6) value added features; 7) space savings. The weaknesses of the e-book are 1) reading on the screen; 2) battery power; 3) security problems 4) permanent 5) lack of standardization; 6) borrow books; 7) hidden costs; and 8) direct costs. Meanwhile, the main strategy is to improve the performance of librarians through efforts job redesign, delegation, skill trainin, and career development. Abstrak Judul artikel ini adalah mengenal e-book di perpustakaan, tulisan ini bertujuan untuk menjelaskan apa saja jenis-jenis, keuntungan serta kekurangan e-book, selanjutnya bagaimana strategi meningkatkan kinerja dalam mengembangkan koleksi e-book . Hasil analisis dari literatur, maka perpustakaan harus mengembangkan koleksi e-book untuk memenuhi harapan pemustaka terhadap informasi. Jenis-jenis e-book dapat dibedakan dari sifat akses, bentuk, dan cara produksi. Keuntungan e-book adalah 1) keterlelusuran cepat; 2) modifikasi lebih sering; 3) portabilitas; 4) variasi; 5) keterbacaan; 6) fitur nilai tambah; 7) penghematan ruang. Sisi kelemahan e-book adalah 1) membaca di layar; 2) daya baterai; 3) masalah keamanan 4) permanen 5) kurangnya standarisasi; 6) meminjam buku; 7) biaya tersembunyi; dan 8) biaya langsung. Sedangkan, strategi utama utntuk meningkatkan kinerja pustakawan melalui upaya job redesign, delegation, skill training dan career development.